The “Redirecting” of International Students: American Higher Education Policy Hindrances and Implications - García, Hugo A.; Villarreal, María de Lourdes (Journal of International Students, 2014)
International student mobility in higher education has gained currency as an important topic in today’s global, political, and economic environment. United States postsecondary institutions are working to expand their international student population to increase revenue and diversity. The current higher education and economic context has produced a “global war” to identify, recruit, and matriculate talented students who have become more mobile when selecting postsecondary education destinations. Thus, in order to provide a clear picture of the current status of international student migration to the United States, we sought to understand the following: 1)prestige as a determining factor in the selection of studying abroad for non-Americans living outside the United States; 2) federal and state financial influences that directly affect institutions’ abilities to enroll foreign students; 3) implications for postsecondary institutions in the United States; and 4) implications for scientific, cultural, and economic advancement for the United States.